Pengaruh Pemasaran Langsung, Kemudahaan Penggunaan, Dan Kepercayaan Terhadap Minat Beli Marine Safety Equipment Pada PT Hong Yi Indonesia - Yuni Rezude Nurita Putri; Wasiman, Wasiman (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2024)
This research aims to explore the influence of direct marketing, ease of use, and trust on interest in purchasing marine safety equipment at PT Hong Yi Indonesia. The population in this study focuses on individuals who are consumers who have made purchases from PT Hong Yi Indonesia, totaling 240 consumers based on the six month period of 2023. The research sample consisting of 150 respondents was selected using a simple random sampling technique based on the Slovin formula. The data analysis process includes multiple linear regression which is tested including data quality testing, classical assumption testing, influence testing and hypothesis testing. The results of multiple linear regression analysis show that direct marketing has an influence of 15.9% on purchasing interest. Ease of use has an influence of 35.0% on buying interest. Trust has an influence of 42.2% on buying interest. Analysis of the coefficient of determination (R2) confirms that overall, direct marketing, ease of use, and trust can explain 85.8% of the variation in purchase intention. Furthermore, the results of the t test and F test show that direct marketing, ease of use, and trust have a positive and significant influence both partially and simultaneously on interest in purchasing marine safety equipment at PT Hong Yi Indonesia.